Bank exit legislationin US, EU and Japanese financial centres - Peik Granlund (Bank of Finland, 2002)
This paper analyses bank exit (ie reorganisation and liquidation) legislation in selected financial centres: New York, London, Frankfurt, Helsinki and Tokyo.The focus is on bank exit legislation applicable to commercial banks.The legislation is analysed from the perspective of bank stakeholders, ie bank creditors, depositors and bank shareholders.The analysis is restricted to those legislative provisions that provide security and rights for stakeholders in case of bank exit.In addition to current conditions, the paper covers the main legislative changes of the latter part of the 1990s.
URN:NBN:fi:bof-20140807143
Keywords: G28; K23; 330; bank; regulation; supervision; reorganisation; liquidation